Hubungan Teknik Menyusui dengan Produksi Asi pada Ibu Primipara - Septi Kurniawati; Srianingsih Srianingsih (Akademi Kesehatan Rustida, 2021)
Breastfeeding technique is one of the factors that affect milk production if the breastfeeding technique is not correct, it can cause sore nipples, then the mother is reluctant to breastfeed, with babies who rarely breastfeed affect the stimulation of breast milk production and exclusive breastfeeding will not work. This study aims to determine the relationship between breastfeeding techniques and milk production in Primiparous Mothers at BPM X. This study used a descriptive correlation research design. The number of samples in this study were 30 people. The sampling technique used was purposive sampling. Data analysis using Chi square test. The results showed that breastfeeding mothers with the correct technique and good milk production were11 (36.7%) and breast milk production (enough & insufficient) were 5 (16.7%), while breastfeeding mothers with incorrect techniques had good milk production. there are 2 (6.7%) respondents and there are 12 (40%) respondents in breast milk production (enough & insufficient). Based on the results of the chi square test, it was found that the P Value was 0.008 (p <0.05) Ho was rejected, it was concluded that there was a relationship between breastfeeding technique and milk production in primiparous mothers.